2018
DOI: 10.4236/ojog.2018.85049
|View full text |Cite
|
Sign up to set email alerts
|

Management of Ectopic Pregnancy in a Broad Ligament and Recurrent Tubal Pregnancy: A Case Report

Abstract: Broad ligament pregnancy is a rare event and always delays in diagnosis. A pregnant woman in early twenties presented for our center. Routine ultrasonography revealed a first trimester abdominal pregnancy. Broad ligament pregnancy was diagnosed intraoperation and treated with laparoscopic resection successfully. The patient has a history of right tubal pregnancy 2 years ago and terminated with Laparoscopic Salpingostomy. According to the long term followed-up for the patient, we found that she had recurrent ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Siow et al injected vasopressin into the broad ligament before starting the excision, the pregnancy was removed, and the surgery was completed uncomplicated [38]. Since then there has been an increase in the reports of broad ligament pregnancies which were managed with laparoscopy [11,17,24,25,30,[60][61][62], while Mo et al in 2018, in the case they reported, managed laparoscopically a broad ligament pregnancy with a hemoperitoneum of about 2800 ml. In most cases coagulation was used to control the breeding.…”
Section: Managementmentioning
confidence: 99%
“…Siow et al injected vasopressin into the broad ligament before starting the excision, the pregnancy was removed, and the surgery was completed uncomplicated [38]. Since then there has been an increase in the reports of broad ligament pregnancies which were managed with laparoscopy [11,17,24,25,30,[60][61][62], while Mo et al in 2018, in the case they reported, managed laparoscopically a broad ligament pregnancy with a hemoperitoneum of about 2800 ml. In most cases coagulation was used to control the breeding.…”
Section: Managementmentioning
confidence: 99%
“…Siow et al injected vasopressin into the broad ligament before starting the excision, the pregnancy was removed, and the surgery was completed uncomplicated [38]. Since then there has been an increase in the reports of broad ligament pregnancies which were managed with laparoscopy [11,17,24,25,30,[60][61][62], while Mo et al in 2018, in the case they reported, managed laparoscopically a broad ligament pregnancy with a hemoperitoneum of about 2800 ml. In most cases coagulation was used to control the breeding.…”
Section: Managementmentioning
confidence: 99%